Influence of Flunixin on the Disposition Kinetic of Cefepime in Goats - Mohamed El-Hewaity (Hindawi Limited, 2014)
The pharmacokinetic profile of cefepime (10 mg/kg b.w.) was studied following intravenous and intramuscular administration of cefepime alone and coadministered with flunixin (2.2 mg/kg b.w.) in goats. Cefepime concentrations in serum were determined by microbiological assay technique using Escherichia coli (MTCC 443) as test organism. Following intravenous injection of cefepime alone and in combination with flunixin, there are no significant changes in the pharmacokinetic parameters. Following intramuscular injection of cefepime alone and in combination with flunixin, the maximum serum concentration was significantly increased in flunixin coadministered group compared with cefepime alone. However, no significant changes were reported in other pharmacokinetic parameters. The result of in vitro protein binding study indicated that 15.62% of cefepime was bound to goat's serum protein. The mean bioavailability was 92.66% and 95.27% in cefepime alone and coadministered with flunixin, respectively. The results generated from the present study suggest that cefepime may be coadministered with flunixin without change in dose regimen. Cefepime may be given intramuscularly at 12 h intervals to combat susceptible bacterial infections.